(untitled) (Research, Society and Development, 2021)
When calves are born, they have metabolic characteristics similar to monogastric ones and hematological parameters vary according to the stage of development. There are still few published data that allow us to safely conclude whether hematological changes in neonates are due to illnesses or due to physiological processes. Thus, this study aimed to evaluate the hematology of 15 crossbred dairy calves from birth to 15 days of age, breastfed by the mother in the first postpartum moment and, later, with colostrum or milk in the morning and in the afternoon, through buckets .From the third day of life, solid food (roughage (hay) and concentrate) was offered. Within 2 hours after birth, with 12 hours, and on days two, three, five, seven, 10, 12 and 15, blood samples were collected in flasks with EDTA for the performance and blood count. There was an increase (p≥0.05) in the red blood cell count between birth and 12 hours and stabilization thereafter. VCM had a reduction in birth at 15 days. The VG was close to the normal limit. On average, fibrinogen concentrations were normal over the 15 days, with the highest values ​​between three and seven days (p <0.01). The lowest and highest PPT averages were 6.28 ± 0.78 g / dL at five days, and 6.65 ± 1.03 at 15 days. Leukocytes and segmented neutrophils were slightly elevated and lymphocytes decreased 12 hours after birth. Then, the values reversed. It is concluded that the observed variations are attributed to physiological changes, with the influence of the age factor being significant.